2018
DOI: 10.3390/insects9020043
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Status and Resistance Mechanisms in Permethrin-Selected, Laboratory Susceptible and Field-Collected Aedes aegypti from Malaysia

Abstract: This study is intended to provide a comprehensive characterization of the resistance mechanisms in the permethrin-selected (IMR-PSS) and laboratory susceptible (IMR-LS) Aedes aegypti strain from Malaysia. Both IMR-PSS and IMR-LS provide a standard model for use in assessing the pyrethroid resistance in field-collected strains collected from three dengue hotspots: the Taman Seri Bayu (TSB), the Flat Camar (FC), and the Taman Dahlia (TD). Two established methods for determining the resistance mechanisms of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
0
15
2
Order By: Relevance
“…Our results contradicted a study conducted in 2011 and also previous studies [20,21,22] revealing that Ae. aegypti populations from Penang were at that time fully susceptible towards pirimiphosmethyl and malathion [50].…”
Section: Resistance Profiles Of Aedes Aegypticontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results contradicted a study conducted in 2011 and also previous studies [20,21,22] revealing that Ae. aegypti populations from Penang were at that time fully susceptible towards pirimiphosmethyl and malathion [50].…”
Section: Resistance Profiles Of Aedes Aegypticontrasting
confidence: 99%
“…Results of the susceptibility bioassay revealed that Ae. aegypti populations from Penang, Kelantan and Selangor exhibit high resistance towards the insecticides from the class of pyrethroid (Type I: permethrin) and organophosphate (pirimiphos-methyl) with the percentage mortality after 24-hour exposure less than 90% confirming these populations are resistant as shown recently [20,21,22].…”
Section: Resistance Profiles Of Aedes Aegyptimentioning
confidence: 73%
See 1 more Smart Citation
“…A study conducted by Fonseca‐González et al () suggested that pyrethroids, organophosphates and DDT used in public health have led to the development of resistance in A. aegypti populations, with variations in the resistance levels, probably depending on the specific selection pressures in each location. Considering the current status of insecticide resistance in A. aegypti , in addition to the evidence of continuous gene flow among A. aegypti populations (Ayres, Melo‐santos, Solé‐Cava, & Furtado, ) and the relatively rapid changes in enzyme levels associated with insecticide resistance (Rasli et al, ), biological control through a L. sphaericus formulation is a suitable alternative.…”
Section: Discussionmentioning
confidence: 99%
“…The results are very different from similar studies of Ae. aegypti from Kedah and Johor states (the northern and southern regions of Malaysia) [47] as well as Yogyakarta [14], in which mutations at 1016 and 989 were common, but 1534 was rare. Within southeast Asia and the Indo-Pacific, the F1534C mutation in Ae.…”
Section: Resistance In the Dengue Vector Mosquitoes In Kuala Lumpurmentioning
confidence: 99%